2015
DOI: 10.1111/vop.12303
|View full text |Cite
|
Sign up to set email alerts
|

Blindness in a wild American black bear cub (Ursus americanus)

Abstract: An approximately six-month-old wild American black bear (Ursus americanus) was found wandering in Saskatchewan and was presented to the Veterinary Medical Centre of the Western College of Veterinary Medicine for apparent blindness. Clinical examination confirmed an inability to navigate a photopic maze, bilateral tapetal hyper-reflectivity, fundi devoid of retinal vessels, and small pale optic nerve papillae. Single-flash electroretinography revealed A and B-wave amplitudes of approximately 40 and 140 microvol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…A nonsuppurative encephalitis was identified in these animals via histopathology, but at this time, the causative agent remains unclear. However, during this investigation, herpesviruses were considered a potential cause, as ursine encephalitis cases have been linked to alphaherpesviruses (Dombrowski et al, 2016). Investigations using degenerate PCR primers, both at the OVDL and at Michigan State University VDL, resulted in amplification of DPOL DNA sequences with homology to gammaherpesviruses in a variety of tissues and in bears with and without evidence of neurologic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A nonsuppurative encephalitis was identified in these animals via histopathology, but at this time, the causative agent remains unclear. However, during this investigation, herpesviruses were considered a potential cause, as ursine encephalitis cases have been linked to alphaherpesviruses (Dombrowski et al, 2016). Investigations using degenerate PCR primers, both at the OVDL and at Michigan State University VDL, resulted in amplification of DPOL DNA sequences with homology to gammaherpesviruses in a variety of tissues and in bears with and without evidence of neurologic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Herpesvirus infection in bears has rarely been documented. Recovery of viral sequences corresponding to the alphaherpesviruses, such as equine herpesvirus 1 (EHV1) and equine herpesvirus 9 (EHV9), have been published in case reports involving captive ursid mortalities (Dombrowski et al, 2016). An investigation of squamous cell carcinomas revealed the presence of a gammaherpesvirus in multiple captive sun bears (Heloarctos malayanus) (Lam et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Kodiak bear ( Ursus arctos mittendorfi ) has an optic disc that is small, round and non‐myelinated 3. However, to the authors’ knowledge, ocular disease in the ursid species is poorly reported on, with only chronic keratitis,4 nodular fasciitis5 and a single case of congenital multifocal retinal dysplasia and retinitis described 6…”
Section: Introductionmentioning
confidence: 99%
“…Progressive hereditary retinal degeneration have also been documented in a number of species,10 16 25 with some species having specific genetic mutations identified that are predisposing 25 26. Finally, there are reports in many species, including another ursid, the American black bear ( Ursus americanus ) of bilateral symmetrical retinal degenerations of unknown aetiology 6 27–29…”
Section: Introductionmentioning
confidence: 99%
“…There are few scientific reports about ocular diseases in the bears [2,10,12]. Hartley reported about ocular disease in bear [6].…”
mentioning
confidence: 99%